PO11 | Neutrophil cathepsin G and risk of cardiovascular events in patients with diabetes mellitus (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aims: Type 2 diabetes mellitus (T2DM) is a major risk factor for atherosclerosis and cardiovascular events (CVEs), partly due to increased platelet activation and inflammation. Neutrophil-derived cathepsin G (CatG), a prothrombotic protease, may play a role in this process by promoting platelet aggregation. However, its association with CVEs in T2DM has not been previously explored. This study aimed to evaluate whether circulating CatG levels independently predict CVEs in patients with T2DM.